Exploring The Disparity of Public Facilities in The Central Java Province - Alinka Pramesthi; Fafurida Fafurida (Universitas Negeri Malang, 2024)
The significant difference between the number of public facilities in regencies/cities and the number of public facilities in Central Java Province, which is feared to result in high inequality, is the focus of this study. The objective of this research is to determine the level of inequality in public facilities and the factors that influence the inequality of public facilities in Central Java Province. Secondary data is utilized and analyzed using the Modified Williamson Index approach and Multiple Regression Analysis. The variables employed include population growth rate, transfer income, and the Human Development Index (HDI). The analysis of the Modified Williamson Index reveals an inequality level of public facilities in Central Java Province of 0.21. The highest level of inequality in public facilities is found in Cilacap Regency, Boyolali Regency, and Kebumen Regency. The factors influencing the inequality of public facilities include the significant variable of transfer income in relation to the level of inequality in public facilities. However, the variables of population growth rate and the Human Development Index (HDI) are not significant factors in relation to the inequality of public facilities.